Understanding community member and health care professional perspectives on gender-affirming care-A qualitative study. - Stephanie Loo (Public Library of Science (PLoS), 2021)
Background Transgender and gender diverse (TGD) people experience significant barriers to accessing affirming health services. There is a paucity of literature examining how both community members and health care professionals (HCPs) understand potential causes and solutions for these barriers, particularly in non-urban settings. Objective We present the first systematic examination of perspectives from community members and HCPs regarding barriers to and solutions for promoting access to gender-affirming health care. Design Study activities were conducted through the Plan and Act for Transgender Health (PATH) Project, a health needs assessment of TGD people. Community members in the catchment area were recruited to participate in focus group discussions about access to gender-affirming health care and optimal health service delivery models in March-October 2019. HCPs were recruited to participate in focus group discussions or in-depth interviews about experiences working with TGD clients. Data were analyzed using an inductive grounded theory approach. Setting 25 rural counties in Massachusetts, New York, Connecticut, Vermont, and New Hampshire. Participants Study participants included 61 adult TGD community members and 23 HCPs working in the catchment area. Results Both community members and HCPs spoke of the need for connectedness and linkages among disparate health system components for gender-affirming health care. Participants expressed this priority through calls for systems-level improvements within existing services (e.g., expanded data collection, expanded mental health services, inclusive and affirming health care environments, and TGD staff). They also expressed the need for expanded TGD community outreach and engagement (e.g., incorporation of a patient feedback process, TGD health navigators, and resource mapping). Limitations Findings specifically reflect the perspectives of community members and HCPs in the rural New England area. Furthermore, the study sample was predominantly White non-Hispanic. Conclusion Interventions to achieve accessible gender-affirming health care must address the diverse perspectives and needs of both community members and HCPs.